Looking to the Future: Medical Students' Views on Health Care Reform and Professional Responsibility. (September 2019) - Rook, Jordan M.; Winkelman, Tyler N.A.; Fox, Jacob A.; Pierce, Jacob B.; Oot, Antoinette R.; Blum, James R.; Feuerbach, Alec M.; Shahu, Andi; Goldman, Max L.; Kopp, Zoe; Duffy, Eamon; Robledo-Gil, Talia; et al.
Abstract : Purpose: Although medical students will influence the future U.S. health care system, their opinions on the Patient Protection and Affordable Care Act (ACA) have not been assessed since the 2016 presidential election and elimination of key ACA provisions. Understanding medical students' views on health care policy and professional obligations can provide insight into issues that will be shaped by the next generation of physicians. Method: From October 2017 to November 2017, the authors conducted an electronic survey of medical students from seven U.S. institutions to elicit opinions regarding the ACA and their professional responsibility to address health policy. Participant demographics and responses were tabulated, and multiple logistic regression models were used to assess the associations of demographic characteristics with student opinions. Results: Completed surveys were returned by 1, 660/4, 503 (36.9%) eligible medical students. Respondent demographics were similar to national estimates. In total, 89.1% (1, 475/1, 660) supported the ACA, and 82.0% (1, 362/1, 660) reported that they understood the health care law. Knowledge of the law's provisions was positively associated with support for the ACA ( P < .001). Most students (85.8%; 1, 423/1, 660) reported addressing health policy to be a professional responsibility. Political affiliation was consistently associated with student opinions. Conclusions: Most medical students support the ACA, with greater levels of support among medical students who demonstrated higher levels of objective knowledge about the law. Furthermore, students indicated a professional responsibility to engage in health policy, suggesting that tomorrow's physicians are likely to participate in future health care reform efforts. Abstract : Supplemental Digital Content is available in the text.